Challenges por prevention of prostate cancer in transgender women (Research, Society and Development, 2023)
This study aimed to describe the challenges for prostate cancer prevention in transgender women. For the elaboration of this work, a narrative review of the literature was used that analyzed national and international scientific studies, during the period from 2015 to 2021. Considering the object of the study, initially the articles referring to the theme addressed were searched in the database data from Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, U.S. National Library of Medicine (PubMed), and Medical Literature Analysis and Retrieval System Online. Thus, the following descriptors were used combined with the Boolean operator AND: transgender people, prostate cancer and primary prevention. The review was divided into prostate cancer in transgender women and the challenges for prostate cancer prevention in transgender women. Finally, it is necessary to understand the epidemiology of prostate cancer and the specific prevention needs in the transgender population and to adopt public health policies that include this public in the prevention strategy.